PROSES INOVASI PELAYANAN KOMUNITAS DIGITAL PEMERINTAH KOTA SEMARANG “SEMARANG DIGITAL KREATIF (SDK)” DI SEMARANG - Ira Rahmawati; Endang Larasati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
The development of digital technology demands the society to be able to compete in facing the digital era. In facing the competition in the digital era, the government of Semarang tries to prepare the youth to be able to think creatively and innovatively. Along with the massive development of communities in Semarang, the government of Semarang is involved in helping the communities to develop their hobbies and talents through a digital community namely “Semarang Digital Kreatif (SDK)”. “Semarang Digital Kreatif (SDK) is an innovation made by the government of Semarang in order to provide a place (co-working space) for communities to channel their hobbies and talents with free and internet-based facilities which include meeting room, start up and private room. The facilities provision is intended to encourage the communities and the youth in order to create a product and to develop entrepreneurship. This research uses descriptive method of qualitative approach. The result of this research can be seen from the innovation process of “Semarang Digital Kreatif (SDK)” digital community service through three aspects: opportunity identification, adoption and implementation. In the innovation process of digital community service, there are factors that facilitate and factors that impede the innovation. Factors that facilitate the innovation of “Semarang Creative Digital (SDK)” digital community service are human resource factor and cultural factor. Meanwhile, factors that impede it are the absent of appreciation, the over-dependence on high performer, the inability to face the risk of a change and administration impediment.